Environmental impact on the building envelope: An architectural analytical study of heat Exchange in new mosque design in Baghdad/ Akeel Noori Abdul Hameed al Mulahiwaish - Akeel Noori, Abdul Hameed al Mulahiwaish (2004)
An efficient building design involves not only functional aspects with respect to structural and space utilization but also environmental aspects and energy considerations. Architectural design is influenced by the actual thermal behavior of building components, and this depends not only on their steady and periodic thermal characteristics but also on exposure effects, orientation, surface colour and the climate parameters of the location. All these parameters enter into heat transfer computations in a complex manner. The design data and criteria should be produced in a rational way for each location, so that architects and engineers can confidently apply them in their design calculations, and to enable precise evaluation of the influence of various design parameters on the overall thermal performance of buildings. The present work is carried out with an objective of first, evaluating: the thermal characteristics of opaque and transparent parts of the new mosque "musalla " envelope in Baghdad, the impact of sol-air temperatures, heat gain factors and the U- alue of envelope section components. Secondly, it aims to assess the architectural criteria for appropriate thermal design of mosques. The research covers a survey of the design, construction features, and comfort levels in new mosques, and the definition of the "model musalla", as well as the identification and thermal assessment of the typical "model musalla" taking into consideration, urban planning, available material skill and other religious criteria. Computer simulations of thermal conditions; modification for design, building ele ments and construction are also covered by the research.The finding and conclusion of the impact of simulation changes are stated as well as recommendation given for possible future mosque and design strategy. The findings show that HVAC systems entail capital, functional and maintenance costs whereas the passive musalla building consumes less energy as well as being more likely to be in sympathy with the environment. Architectural design and construction of the new musalla envelope in Baghdad are thermally inefficient in protecting the inner space from climatic fluctuations. Therefore, the existing new musallas are not within thermal comfort level. To achieve and maintain that, applying architectural and construction alternatives on the musalla envelope contributes to controlling heat exchange through it as well as enhancing its thermal behaviors that contribute to getting internal thermal balance.